2020
DOI: 10.13189/ujer.2020.081701
|View full text |Cite
|
Sign up to set email alerts
|

Validity Test of the Family Supported Collaborative Learning (FSCL) Model to Instill Character Values to Junior High School Students

Abstract: Educational strategies provide opportunities to create learning where students can collaborate with others (Education should be collaborative). This can be carried out through developing FSCL learning model. This research aimed to test the validity of the FSCL model product to instill the character values to junior high school students in Ponorogo Indonesia. The method used in this research was a research and development with three stages of preliminary study, product development and product testing. The valid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…As the formation of social behavior starts from the surroundings of the human being who interacts with it [35]. The importance of psychosocial life, as a key component of successful relationships and interactions with others, must be emphasized, starting from childhood [36][37][38]. A large proportion of a child's perception of future life is determined by his or her childhood.…”
Section: Discussionmentioning
confidence: 99%
“…As the formation of social behavior starts from the surroundings of the human being who interacts with it [35]. The importance of psychosocial life, as a key component of successful relationships and interactions with others, must be emphasized, starting from childhood [36][37][38]. A large proportion of a child's perception of future life is determined by his or her childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Validity test results were obtained from validation sheets given to experts when examining the instrument [18]. The instruments that have been examined by experts are then described and used as an improvement material to get the right instruments.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the question items belonging to the comprehension category (C2), it was found that there were 10 questions, namely Q5, Q8, Q23, Q34, Q36, Q39, Q42, Q43, Q45, and Q60. This is because, in the ten questions (see sample in Table 11), the form of the command indicates the aspect of understanding, which operationally refers to the activities of exemplifying, classifying, concluding, comparing, and explaining (Budiwan, Hidayatullah, Yusuf, & Asrowi, 2020). For example, the Q5 question requires students to read the previous text, summarize the results of their reading, then they can choose the right answer.…”
Section: Understandingmentioning
confidence: 99%